Cryoprotective Efficiency of Media Combining Oxyethylated Methylcellosolve and Dimethyl Acetamide during Freeze-Thawing of Human Erythrocytes - Nikolenko, Aleksandra V.; Vyazovska, Olga V.; Chekanova, Valentina V. (Problems of Cryobiology and Cryomedicine, 2013)
Using the media, which combine cryoprotectants being chemicals of different classes, is prospective when developing cryoprotective solutions to cryopreserve erythrocytes. This investigation was performed to evaluate cryoprotective activity of media combining representative of polyols, non-penetrating cryoprotectant oxyethylated methyl cellosolve with polymerization degree of n = 33–35 (OEMCn=33–35) and the representative of amides, penetrating cryoprotectant dimethyl acetamide (DMAc). Combinations of OEMCn=33–35 and DMAc in concentration (w/w) ratios 1:1 (10 and 10%); 2:1 (10 and 5%); 3:1 (15 and 5%); 4:1 (20 and 5%); 5:1 (25 and 5%) were compared with 20 and 30% OEMCn=33–35 solutions. Addition of DMAc to cryoprotective media based on OEMCn=33–35 increased the post-thaw osmotic resistance of erythrocytes. Application of the media combining OEMCn=33–35 and DMAc in ratios of 1:1 (10 and 10%) and 3:1 (15 and 5%) provided a high post-thaw survival of erythrocytes. Osmotic fragility of erythrocytes was found to correlate with the indices of intracellular content of potassium and sodium and with hematocrit value during exposure of the cells in cryoprotective media. Probl Cryobiol Cryomed 2013; 23(4):297–308.